"I suppose I'll be patching you up, as usual": Women's roles and normative femininity in a team-based video game. (May 2022) - Austin, Jessica
Women are often viewed as outsiders in the videogaming environment, particularly in first-person shooter games. Perceived infringement on an overwhelmingly masculine space pushes women to the margins of online team-based games, where gender norms inform the presumption that they play supportive roles that are viewed as passive and unskilled rather than actively contributing to team objectives. This study explores why women continue to play these roles, even as they are belittled, how societal expectations of women translate to the gaming space, and consequences for gender as a social structure. Findings suggest similarities to gendered labor in that women report feeling obligated to shoulder tasks that nobody else desires, much in the same way that professional work characterized as feminine is devalued. In addition, women must perform emotion work as they game by hiding their role preferences, feeling shame at fulfilling harmful gender stereotypes, and justifying their utility.